2020
DOI: 10.1021/acs.joc.0c00922
|View full text |Cite
|
Sign up to set email alerts
|

Aphananoid A is an Anti-Inflammatory Limonoid with a New 5/6/5 Fused Ring Featuring a C24 Carbon Skeleton from Aphanamixis polystachya

Abstract: Aphananoid A, a limonoid which features a rare C 24 appendage and new 5/6/5 fused-ring framework, was obtained from Aphanamixis polystachya. The planar structure as well as the absolute configuration was identified based on extensive spectroscopic analysis and electronic circular dichroism calculations. The biogenetic pathway of aphananoid A was also speculated, which arises from the triterpene by the 3,4-seco-7,8-seco-6,8 cyclo-7,30-decarbon key pattern. In addition, bioassays indicated that aphananoid A inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…The antiinflammatory potential of hederacoside-C against osteoarthritis was also evaluated (H. C. Aphanamixis polystachya as a novel 5/6/5 fused ring featuring a C 24 carbon skeleton (B. J. Yang, Fan, et al, 2020), was reported to reduce the levels of TNF-α, IL-6, IL-1β, TLR4, and NF-κB.…”
Section: Saponins-compounds 205-247mentioning
confidence: 99%
See 1 more Smart Citation
“…The antiinflammatory potential of hederacoside-C against osteoarthritis was also evaluated (H. C. Aphanamixis polystachya as a novel 5/6/5 fused ring featuring a C 24 carbon skeleton (B. J. Yang, Fan, et al, 2020), was reported to reduce the levels of TNF-α, IL-6, IL-1β, TLR4, and NF-κB.…”
Section: Saponins-compounds 205-247mentioning
confidence: 99%
“…Limonoid azadirachtin A ( 272 ), isolated from Azadirachta indica , markedly reduced the levels of TNF‐α, IL‐6, IL‐1β, TLR4, and NF‐κB (He et al, 2020) (Figures 29 and 30). Aphananoid A ( 273 ), isolated from Aphanamixis polystachya as a novel 5/6/5 fused ring featuring a C 24 carbon skeleton (B. J. Yang, Fan, et al, 2020), was reported to reduce the levels of TNF‐α, IL‐6, IL‐1β, TLR4, and NF‐κB.…”
Section: Antiinflammatory Activity Of Natural Triterpenesmentioning
confidence: 99%
“…Limonoids (462)(463)(464)(465)(466)(467)(468) are derivatives of compound (461) but differ in substitution at C1 and C23. The furan ring at C17 in 28-deoxonimbolide is replaced by α,β-unsaturated-21-hydroxy γ-lactone ring in limonoid (469). Nimbolide B (470) differs from compound (469) in additional keto carbonyl at C28.…”
mentioning
confidence: 99%
“…Limonoids (462-468) are derivatives of compound (461) but differ in substitution at C1 and C23. The furan ring at C17 in 28-deoxonimbolide is replaced by α,β-unsaturated-21-hydroxy γ-lactone ring in limonoid (469). Nimbolide B (470) differs from compound (469) in additional keto carbonyl at C28.…”
mentioning
confidence: 99%
“…The furan ring at C17 in 28-deoxonimbolide is replaced by α,β-unsaturated-21-hydroxy γ-lactone ring in limonoid (469). Nimbolide B (470) differs from compound (469) in additional keto carbonyl at C28. Compounds (471,472,473) are structural analogs of compounds (469, 460, 467) respectively differing in substitution at C17.…”
mentioning
confidence: 99%